The design of an optimal, dynamic, multi-hop telemetry network - Nicholson, Gareth Andrew (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.